2014
DOI: 10.1007/s12070-014-0743-1
|View full text |Cite
|
Sign up to set email alerts
|

Relative Etiological Importance of Adenoid Hypertrophy Versus Sinusitis in Children with Persistent Rhinorrhoea

Abstract: Persistent rhinorrhoea is a common, yet often neglected, problem among Indian children. This study was designed to evaluate the relative etiological importance of adenoid hypertrophy versus sinusitis in children with persistent rhinorrhea. Additionally, the association between S. pneumoniae colonization and adenoid hypertrophy was studied. Children aged 1-14 years with persistent rhinorrhea underwent clinical evaluation, rigid nasal endoscopy and xrays of the nasopharynx and paranasal sinuses to ascertain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“… 8 14 Additionally, the effect of adenoid for sinusitis may be secondary to mechanical obstruction of the nasopharynx. 4 Therefore, some authors suggested that adenoidectomy should be performed to remove mechanical obstruction of the nasopharynx or infection focus in chronic or recurrent sinusitis patients. 13 14 19 However, they had some limitations due to small participant size, 13 19 significant follow up loss, 19 and lack of investigation about subjective sinusitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 14 Additionally, the effect of adenoid for sinusitis may be secondary to mechanical obstruction of the nasopharynx. 4 Therefore, some authors suggested that adenoidectomy should be performed to remove mechanical obstruction of the nasopharynx or infection focus in chronic or recurrent sinusitis patients. 13 14 19 However, they had some limitations due to small participant size, 13 19 significant follow up loss, 19 and lack of investigation about subjective sinusitis symptoms.…”
Section: Discussionmentioning
confidence: 99%
“… 3 The adenoids are known to cause either mechanical obstruction or stasis of secretions or may be a nidus causing repeated episodes of upper respiratory infection. 4 Additionally, the adenoid can serve as a reservoir of pathogenic bacteria and recurrent or persistent adenoiditis is associated with common diseases of neighboring structures including sinusitis. 5 In many children, adenoid hypertrophy and sinusitis are known to coexist.…”
Section: Introductionmentioning
confidence: 99%